El principio de igualdad y la corresponsabilidad parental en el Ecuador - Guerrero Checa, Stephany Samanta (2025)
This research focuses its analysis on the principle of equality and its application within the figure of parental co-responsibility in the Ecuadorian legal system. The main problem is that in Ecuador this principle is contemplated within its legal essence but there is no materialized norm that reflects true equality between parents. That is why, within the research, the general objective was to propose legal criteria that show that the principle of equality and parental co-responsibility in Ecuador violates the content of Art. 100 of the Code of Children and Adolescence. For this, a methodology with a qualitative research approach was used, because primarily the intrinsic and subjective characteristics of the study variables are analyzed; As well as through the analysis of the legal system, it was possible to show that article 100 of the Code of Children and Adolescents guarantees parental co-responsibility in light of the principle of equality, but there is no rule or procedure that makes this precept justiciable.